Key issues in health economics - Mooney, Gavin H. (Harvester Wheatsheaf, 1994)
A companion volume to "Economics, Medicine and Health Care", this book is aimed at health service professionals. It provides a wide range of practical health care issues. Topics covered include alternative methods of financing health care and setting health care priorities